APPLICATION OF THE NEWEST TECHNOLOGIES IN ARCHAEOLOGICAL RESEARCH IN UKRAINE - Іваненко, Ростислав; Сапицька, Олена (SWorldJournal, 2024)
The paper provides examples of using the latest technologies in the modern archaeology of Ukraine. It is noted that this opens up broad prospects for the development of archaeology and the preservation of Ukraine’s historical and cultural heritage. The in